2017
DOI: 10.1097/mlr.0000000000000746
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Perceived Race-based Discrimination and Contraceptive Use Among Women Veterans in the ECUUN Study

Abstract: Objective To describe perceived race-based discrimination in VA healthcare settings and assess its associations with contraceptive use among a sample of women Veterans. Methodology This study used data from a national telephone survey of women Veterans aged 18–44 receiving healthcare in VA who were at risk of unintended pregnancy. Participants were asked about their perceptions of race-based discrimination while seeking VA healthcare and about their contraceptive use at last heterosexual intercourse. Logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Consistent with the current literature, we found that the perception of race-related fear from doctors or nurses toward patients was the least reported type of perceived discrimination [12, 30, 34, 35]. In previous studies, perceiving that providers were “not listening” was the most commonly reported item on the DMS [12, 19, 29, 30, 34]; however, in our study, receiving “poorer services” was most frequently reported.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the current literature, we found that the perception of race-related fear from doctors or nurses toward patients was the least reported type of perceived discrimination [12, 30, 34, 35]. In previous studies, perceiving that providers were “not listening” was the most commonly reported item on the DMS [12, 19, 29, 30, 34]; however, in our study, receiving “poorer services” was most frequently reported.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies using the DMS scale reflect a wide range of prevalence rates, from 8% of female veterans [34] to over 60% of those included in a convenience sample of African American adults in northern Ohio [12] and a sample of HIV patients [29]. Consistent with the current literature, we found that the perception of race-related fear from doctors or nurses toward patients was the least reported type of perceived discrimination [12, 30, 34, 35]. In previous studies, perceiving that providers were “not listening” was the most commonly reported item on the DMS [12, 19, 29, 30, 34]; however, in our study, receiving “poorer services” was most frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is troubling that, among our sample of patients with pain, over one in five who perceived discrimination described healthcare experiences in which they felt overtly stigmatized. The prevalence of perceived discrimination observed in this study is within the wide range observed in prior studies that have assessed perceived racial/ethnic discrimination in VA healthcare settings [4,5,[37][38][39]. Although the overall prevalence varies across studies depending on the targeted patient population and the measure used to assess perceived discrimination [5], a common pattern observed across the literature is that racial/ethnic discrimination is more frequently reported by racial/ethnic minority patients compared to White patients, as was the case for our study.…”
Section: Plos Onesupporting
confidence: 74%
“…As expected, perceived race-based discrimination was reported by higher proportions of black and Hispanic women compared with white women (11.3 and 11.2% vs. 4.4%, respectively; p < 0.001). 39 These findings underscore the fact that racial differences in contraceptive use are driven by a variety of variables, many of which clinicians may be able to elicit during nuanced counseling to improve the provision of contraceptive care and ensure that method selection is the result of informed and preference-concordant decision making.…”
Section: Vulnerable Populationsmentioning
confidence: 95%